Psychological Readiness Education and Preparation Before Childbirth - Marbun, Uliarta; Irnawati, Irnawati (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
The process of childbirth is basically a physiological thing experienced by every birthing mother, as well as an amazing thing for mothers and families. However, worry, fear and anxiety will arise when entering labor. Feelings of fear can increase physiological and psychological responses, such as: pain, muscles become tense and the mother becomes tired quickly, which will ultimately hinder the labor process. Objective: to reduce psychological health problems faced by pregnant women is with a class program for pregnant women to prepare pregnant women physically and mentally. Method: providing education to pregnant women related to psychological preparation of pregnant women before labor and what preparations are needed before labor. Result: Participants of community service activities aimed at pregnant women and families went smoothly with good and positive responses shown by all activity participants seen from the enthusiasm of participants listening during the presentation of the material given and actively asking questions related to psychological readiness so that pregnant women are not afraid before labor and other preparations needed during labor. Conclusion: the importance of psychological readiness for pregnant women and other preparations before childbirth with a class program for pregnant women